2008
DOI: 10.1007/s00468-008-0275-y
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic changes and oxidative stress caused by iron ore dust deposition in the tropical CAM tree Clusia hilariana

Abstract: The effect of iron solid particulate matter (SPM Fe ) deposited onto soil and leaves on photosynthesis and oxidative stress was evaluated in Clusia hilariana, a CAM tropical tree of high occurrence in Brazilian restingas. Significant increases in iron content were found in plants exposed to SPM Fe applied onto leaf and soil surfaces. However, only the application of SPM Fe on leaves of C. hilariana caused significant reductions in some evaluated characteristics such as photosynthetic rate, stomatal conductance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 26 publications
(35 reference statements)
2
19
0
Order By: Relevance
“…In previous studies, asymptomatic leaves of this species showed physiological alterations in response to the SPM Fe deposition, such as reduction of the pigment levels, compromising of the photosynthetic processes, and the increase of the leaf iron level (PEREIRA et al, 2009). Among possible causes, the authors have suggested it was due to the obstruction of the stoma and the iron absorption of the iron at leaf level, as the soil was covered during the SPM Fe applications (PEREIRA et al, 2009). However, the leaf structural and micromorphological analyses can be the key for answering these questions.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…In previous studies, asymptomatic leaves of this species showed physiological alterations in response to the SPM Fe deposition, such as reduction of the pigment levels, compromising of the photosynthetic processes, and the increase of the leaf iron level (PEREIRA et al, 2009). Among possible causes, the authors have suggested it was due to the obstruction of the stoma and the iron absorption of the iron at leaf level, as the soil was covered during the SPM Fe applications (PEREIRA et al, 2009). However, the leaf structural and micromorphological analyses can be the key for answering these questions.…”
Section: Introductionmentioning
confidence: 78%
“…The experiment lasted 45 days, and the deposition simulation was performed at 8:00 in the morning. Inside the chamber, the amount of particulate matter deposited on the plants reached an average of 2.14 mg cm -2 day -1 (PEREIRA et al, 2009). In the control treatment, the plants were not subjected to deposition of iron particulate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations